Capturing movement patterns during procedural control activities in air traffic control / S.M.B. Abdul Rahman ...[et al.] - Abdul Rahman, S.M.B; Halim, H. R.; Sidik, M. F. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
The Air Traffic Controller (ATCo) is responsible for monitoring aircraft movement within a specified airspace by using radar and/or procedural control as its monitoring instrument. Research looks at the possibility of using human motion analysis in capturing signs of distress during sole procedural monitoring activity by the ATCo. In this research, it is hypothesized that a higher mental task load during a procedural control monitoring activity will be exhibited through more rapid or unusual body movement. To analyze this, a human-in-the-loop (HITL) experiment was conducted to monitor the ATCo physical response, specifically upper body movements during control activities. This was done using KINECT® as the device to monitor the movement. Based on the results, the subjects did exhibit a change in frequency or extremity of their upper body movement during the course of the experiment. However, this could be either due to task-related or stress-related body movement. Thus, a more elaborate study on baseline subject-scenario body movement during control activities for each controller is needed in order to clearly isolate signs of high mental task load or distress.